Microarchitecture of a MultiCore SoC for Data Analysis of a Lab-on-Chip Microarray. (28th July 2008) - Kornaros Kornaros, G. G.; Blionas Blionas, S. S.
Abstract : This paper presents a reconfigurable architecture of a lab-on-chip (LoC) microarray device capable to process data either in genotyping or in gene expression applications in a fraction of the time that is required by the usual software methods running on a standard computer. The entire LoC consists of a microfluidics part for the sample preparation and hybridization, a microsystem part including the application specific array of sensors for the electronic detection, and finally a reconfigurable processing part for the data analysis. The proposed data processing and analysis electronic module are an embedded multicore reconfigurable system-on-chip designed to analyze data from the forthcoming high-density oligonucleotide microarrays. The proposed architecture employs reconfigurable technology and has the capacity to process data from microarrays of various sizes from small size ones used in genotyping up to large-scale gene expression arrays. Additionally, the embedded processing cores feature reconfigurable circuitry for implementing the intense part of the processing, supplementing the various computational needs of the diverse applications for microarray real-time data processing and for a scalable reconfigurable architecture to handle also the future high-density microarrays.